The association between chronic severe pain and neuroticism personality trait among patients on methadone maintenance therapy in Alor Star, Kedah - Koh, Chin Hong (2017)
Pain is very commonly reported among previous heroin users on methadone maintenance therapy (MMT) with the prevalence of chronic severe pain (CSP) of 37-48.2% being reported. The symptom causes distress and disability, and adversely affect patients’ quality of life, addiction treatment outcome and exacerbates their ambivalence towards MMT. In general, neuroticism personality trait has been shown by various studies to be associated with CSP, but similar association has yet been explored in MMT patients.Current study aim to assess the prevalence of CSP among patients on MMT, and to examine whether neuroticism is significantly associated with CSP in this group of patients.This is a cross-sectional study, utilizing validated Malay versions of Brief Pain Inventory (BPI) for pain measurement, Big Five Inventory (BFI) to measure neuroticism, Beck’s Depression Inventory (BDI) for measurement of depressive symptoms, and Beck’s Anxiety Inventory (BAI) for measurement of anxiety symptoms. All rating instruments mentioned are self-rated instruments. Sample size is determined using proper sample size calculation, and universal sampling method is applied for subject recruitment. Samples were collected from two MMT centres in Alor Star. By using Multiple Logistic Regression analyses, Neuroticism score (p<0.001), BAI score (p<0.012) and regular use of over-the-counter analgesics (p<0.016) were found to be statistically significant in association with CSP, with adjusted Odds Ratio of 1.60 (95% CI 1.27, 2.12), 1.44 (95% CI 1.08, 1.93), and 3.56 (95% CI 1.27, 10.01), respectively. Multicollinearity was not detected. However, interaction was noted between neuroticism score and BAI score (p=0.028). Hence, the interaction was included into the analysis of fitness of final model. The fitness of this final model was confirmed using Hosmer-Lemeshow test (p=0.282), classification table (overall correctly classified percentage= 83.4%), and area under the receiver operating characteristic (ROC) curve test (87.9%). It was interesting to note that the prevalent of daily usage of kratom product was over 40% in the sample. Neuroticism score is positively associated with CSP among patients on MMT, whereby with every one point increment in neuroticism score, there is 60% higher odds of having CSP. Though it is tempting to conclude that high neuroticism score predict CSP development among patient on MMT, the author recognizes the limitations of current cross-sectional study design in establishing the nature of the association. Other significant associative factors are BAI score and regular use of over-the-counter analgesics. For every one point increment in BAI score, there is 44% higher odds of patient having CSP; and if an MMT patient use OTC analgesics for at least 3 times a week, the odds of having CSP is 3.6 times compared to those not using OTC regularly. The results suggest that, firstly, addressing anxiety in patient might help to improve CSP, and unaddressed anxiety in patient with chronic pain might in fact adversely affect the efficacy of chronic pain intervention and MMT outcome. Besides, the strong association between OTC analgesics usage and CSP suggested that when CSP among this group of patients was not adequately addressed, patient resorted to OTC analgesics to relieve their pain. OTC use as a way of self-medication was reported by studies to be common, and the practice actually exposes the patients to adverse drug reactions, which is avoidable. In the case of MMT, drug-to-drug interaction of methadone with OTC analgesics could be fatal. Over 40% of the study subjects reported use of kratom product daily. Though its association with CSP was not statistically significant, its implication to our MMT patients cannot be ignored, as kratom has been increasingly reported locally, as well as globally, as an emerging illicit substance with high abuse potential.